Curiosity, responsibility, hospitality: Scenes of interreligious friendship - Houck, Anita (Missiology, 2019)
Three themes in interreligious friendship are illustrated through stories from the author's childhood and adulthood. Curiosity takes different forms across the life span but can continue to lead to relationships both personal and professional. Responsibility asks that one represent one's own tradition accurately, including in recognizing that no single person can speak for a religion. Hospitality is understood both as interpersonal welcome and, drawing from Catherine Cornille, as recognizing and welcoming "actual truth" in other religions. Hospitality offers and sustains friendship despite societal obstacles and individual failures. Throughout the life cycle, the experience of envying others' religiosity can both inspire friendship and refine how one understands and practices one's own religious commitments.